(3QhVI GdQGFV aj Yde GdaQGFVs - (3Hf YQHTGg GdYKeGfj (B/ (3YHO GdhgGH Hf CMeOs; (3eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj, SQGL GdOjf CHh WGgQ,J (B598 (3g` ? s
(3ChdgG (B:s
(3hHYO bO bGd YHOGdhgGH HGHf YQHTGg s
(3BNQgG (B:s
(3bO GbJajJ GKQge GdYdi GdMb ef SHbfi GdaVd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
(3JHUQGJ GdCUd (B:s
Keywords: (3Yde GdaQGFVs